Comparative kinematic analysis of enqvist and moya's tennis serve technology - Li, Y.; Zhou, J.; Wang, L. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Serving occupies a more important role in the modern tennis. The tennis serve of two players, Thomas Enqvist and Carles Moya, were filmed in the semifinals of Chengdu Open-ATP Champions Tour and analysed with three-dimensional video analysis. The serve was divided into three stages as follows: throwing ball rising racket stage, backward swing stage, forward swing hitting stage. It is found that: in the first stage, the maximum value of shoulder-hip level projection angle of Enqvist and Moya are 18.5° and 28.7° respectively. In the second stage, Enqvist and Moya's extension range of left knee joint were 55.1° and 34.6°.Their e angular velocity were 182.6°/s and 170.4°/s. In the third stage, Enqvist and Moya's hitting height were 2.23m and 2.15m, Hitting height and body height ratio were 1.18 and 1.13, there are significant differences.